Role of Cooperative in Economic Empowerment of Women - Basyal, Laxmi (Khwopa Journal, 2025)
Economic background is one of the most important elements that influences their access to resources, opportunities, and decision-making power. This paper attempts to assess the key economic features of women and their association with cooperatives in relation to empowerment by age, caste/ethnicity, education, and family income. The aim of this study is to examine the change in economic status of women after their involvement in cooperative. This research focused solely on the economic effects of cooperatives and individual saving and investment to examine the status of women’s empowerment. Primary data were collected from the Parijat Saving and Credit Cooperative Limited in Bhaktapur. Role of cooperatives on women’s economic empowerment is assessed utilizing the data of 238 women aged 18 to 66 years using descriptive and bivariate Chi-square analysis techniques. The findings revealed significant improvements in women’s economic status after their participation in cooperatives. Over 81 percent of women reported improvements in leadership, 84 percent in entrepreneurship, 60 percent in employment status, and 93 percent in overall economic status. Among them, women from the "others" caste groups—such as Kami, Damai, Sunar, and Madhesi and women with no formal education showed the highest percentages of improvement in leadership. Similarly, women from the "others" caste groups and those aged 50 years and above showed greater improvements in entrepreneurship compared to other groups. Likewise, women from the highest income group demonstrated the most improvement in employment status. Additionally, women with no formal education or low levels of education showed greater improvement in overall economic status than women from other educational backgrounds. These findings imply that cooperative involvement significantly enhance the women’s economic status.